Refleksija afirmiranja politologije kot znanstvene vede in njene širše družbene relevantnosti - Banjac, Marinko (Teorija in praksa, 2024)
Political science is constantly self-reflexive as it intertwines with other social sciences and draws specific research practices, methodologies and insights from them. This introspection is crucial because political science studies phenomena from different perspectives, stemming from different research traditions. Understanding its own context and its impact on other disciplines allows political science to better understand its own context and contribute to informed research and debate. The article discusses Bibic’s reflections on the relationship of political science to other social sciences and its social significance, examining its historical conditioning, autonomy and relation to other disciplines. It also considers how Bibič contributed to understanding how political science can add to (political) education theory and practices and to a broader understanding of politics.
Keywords: Bibič, Adolf; družbena vloga znanost; Družbene vede; politics; Politične vede; politika; social role of science